Analisis Surat Al-Fatihah Sebagai Kesatuan Al-Qur’an Perspektif Kitab Ensiklopedi Al-Qur’an Dan Tafsir At-Tanwir - 'Aarifah, Fadhlinaa 'Afiifatul; Saputra, Edriagus (Journal Education And Islamic Studies, 2024)
This paper tries to re-analyze and prove the statement by looking at the interpretation of Dawam Raharjo's own Encyclopedi al-Qur'an and Tafsir at-Tanwir owned by Muhammadiyah institutions. According to the author's analysis, both interpretations have the same method but with different models. Tafsir Encyclopedi al-Qur'an uses a letter thematic model while Tafsir at-Tanwir uses a conceptual thematic model. With different thematic method models, the focus of this paper is to compare and take the common thread of the two interpretations so as to produce more comprehensive analysis and evidence. The research method is qualitative with a thematic study model (maudhu'iy). The findings based on the results of this study are Dawam Raharjo considers al-Fatihah as a short letter which is a summary of the Qur'an by placing the letter as muhkamat verses and the rest of the body of the Qur'an as mutasyabihat verses as explained in Al-Qs. Ali Imron verse 3. Therefore, with the thematic method of letters using the key concepts of Dawam al-Fatihah can serve as a benchmark for the interpretation of other verses so that when facing mutasyabihat verses of the Qur'an can avoid the possibility of deviation of interpretation from the main idea in accordance with al-Fatihah. While Tafsir at-Tanwir builds the argument of al-Fatihah as a unity of the Qur'an with its conceptual thematic method. Tafsir divides al-Fatihah into two major theme concepts, namely the Qur'an as a view of life and the Qur'an as a way of life. The two big theme concepts explain the flow, way and consequences of the Qur'an comprehensively and briefly. Therefore, there must be no doubt that the Qur'an is the overall guidance and guidance of humans in living life with an outline that has been described in Surah al-Fatihah.